Generalized Predictive Current Control (GPCC) for Grid-Tie Three-Phase Inverters - Judewicz, Marcos (2016)
This work proposes a linear generalized predictive current control (GPCC) for grid-connected voltage-source inverters, which presents a fast response to current reference step changes, parameter variation robustness, and low distortion at the output currents, with reduced computational effort. Experimental results on a 10-kW converter connected to a real grid are shown, and the proposed controller is compared against a classical proportional resonant controller.